Linkage Mapping and Comparative Transcriptome Analysis of Firmness in Watermelon (Citrullus lanatus) - Sun, Lei; Zhang, Yushu; Cui, Haonan; Zhang, Lupeng; Sha, Tongyun; Wang, Chaonan; Fan, Chao; Luan, Feishi; Wang, Xuezheng (Frontiers in Plant Science, 2020)
Abstract: Watermelon fruit texture and quality are determined by flesh firmness. As a quality trait, flesh firmness is controlled by multigenes. Defining the key regulatory factors of watermelon flesh firmness is of great significance for watermelon genetic breeding. In this study, the hard-flesh egusi seed watermelon PI186490 was used as the male parent, the soft-flesh cultivated watermelon W1-1 was used as the female parent, and 175 F2 generations were obtained from selfing F1. Primary mapping of the major genes controlling center flesh firmness was achieved by BSA-Seq analysis and molecular marker technology. Finally, major genes were delimited in the physical interval between 6210787 and 7742559 bp on chromosome 2 and between 207553 and 403137 bp on chromosome 8. The content of each cell wall component and hormone was measured, and comparative transcriptome analysis was performed during fruit development in watermelon. The protopectin, cellulose, hemicellulose, IAA and ABA contents were measured, and paraffin sections were made during the three fruit developmental stages. The results revealed that protopectin, celluloses and hemicelluloses exhibited similar trends for flesh firmness, while the IAA and ABA concentrations continued to decrease with fruit ripening. Paraffin sections showed that PI186490 cells were more numerous, were more tightly packed, had clearer cell wall edges and had thicker cell walls than W1-1 cells at every developmental stage. Comparative transcriptome analysis was conducted on RNA samples of flesh during fruit development and ripening in W1-1 and PI186490. The results from the localization interval transcriptome analysis showed that Cla016033 (DUF579 family member), which may influence the cell wall component contents to adjust the flesh firmness in watermelon fruit, was different in W1-1 and PI186490 and that Cla012507 (MADS-box transcription factor) may be involved in the regulation of fruit ripening and affect the hardness of watermelon fruit.